The Relationship Between the Duration of Gadget Use and Students' Ability to Concentrate - Sarah Ajrina Husni Putri; Khaeruddin Bashori; Muh. Samsuddin (Journal Emerging Technologies in Education, 2024)
Background. The use of gadgets is increasing day by day, from children to adults. The use of gadgets certainly has a positive impact and also a negative impact. Children who are still in school will feel the effects of gadget use. The use of gadgets in proper control will have a good effect on the child's growth and development process. But on the other hand, excessive use of gadgets will affect children's development. In addition, it will also affect the social conditions of children in everyday life. Purpose This study aims to determine how much the relationship between the duration of gadget use and students' concentration ability. Gadgets at this time are not a foreign thing, wise use of gadgets will provide benefits for users. The use of gadgets in different durations will have a different impact on their use. Method. The method used in this research is quantitative. Quantitative methods characterized by the use of numbers in the process will help measure the data obtained. Data collection is in the form of distributing questionnaires made in the form of google from. This will make it easier and shorten the time for collection. Google from contains several questions that will be responded to by teachers and students. The statements presented are matters relating to the relationship between gadget use and student concentration. Results. The results of this study explain the relationship between the duration of gadget use and students' concentration levels. Using gadgets wisely in time management will give the impression of not being too dependent and focus is maintained. However, excessive intensity of gadget use will have an impact on student health. Students will fail to focus on learning, even students will experience mental health problems. It takes the right strategy in using gadgets, such as setting the duration of use, access permissions, and many more.   Conclusion his study can be concluded that the duration of gadget use in students will affect the level of concentration. The duration of use that is controlled and not excessive will make students concentrate more. However, excessive use of gadgets and no control from parents or teachers will adversely affect student concentration which will deteriorate.